Implementasi Corporate Social Responsibility (CSR) pada UMKM Kerajinan Perak di Desa Celuk - Setiasih, Ni Putu Eka; Dewi, A.A. Istri Erlika Trisna (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2025)
Celuk Village in Gianyar Regency, Bali is the centre of a high-quality silver craft industry that combines artisan skills and local wisdom. Silver craft production involves a metal plating process that generates solid waste, gas emissions and electrolyte solutions that have the potential to pollute the environment. Both MSMEs strive to be active in business sustainability, which has not been reflected in accounting practices. This shows the urgency of a more effective implementation of corporate social responsibility to support the sustainability of MSMEs. This study aims to analyse the implementation of CSR in two silver craft MSMEs in Celuk Village, namely Yan Yan Silver and Sari Dewi. A qualitative approach was used by collecting data through direct observation and semi-structured interviews. Data was analysed using reduction and triangulation techniques to ensure the validity of the findings. The results showed that Yan Yan Silver implemented good waste management through collecting electrolyte waste in a special place, selling production dust to collectors, and recycling silver scraps. Stable turnover encourages MSMEs to empower the surrounding community by recruiting local labour, contributing to traditional activities, improving public facilities, and collaborating with local artisans. Meanwhile, Sari Dewi emphasises environmental conservation in its production process through the use of pure water and recycling of silver scraps. However, its involvement in social aspects is more limited, reflected in its competency-focused recruitment system and minimal participation in social activities outside the company. The findings suggest that Yan Yan Silver prioritises community-based social responsibility, while Sari Dewi focuses on environmental sustainability